Associations between the occurrence of lameness, number of orthopaedic blocks used by hoof trimmers and management risk factors in dairy cow herds - Gudaj, Richard; Brydl, Endre; Komlósi, István (Animal Welfare, Etológia és Tartástechnológia (AWETH), 2012)
A 5-point locomotion scoring system was used to investigate risk factors for elevated locomotion scores and increased number of blocks used by trimmers among 11 422 dairy cows on 25 farms in Hungary. Each of the farms was visited twice between May and December 2010 and between May and December 2011. At each visit, all milking cows were scored for locomotion by a single observer. Farms were grouped according to their management (which sometimes changed in two years) and prevalence of lameness. Correlations, analysis of variance and chi-square tests were constructed to identify factors associated with elevated mean locomotion score (increased abnormality). Risk factors for increased locomotion score were: increased number of foot baths per week, decreased number of extra free stalls, decreased BCS, dirtier bedding, non-grooved feed yards, limited access to water, old-fashioned, square feeders and milking parlours with steps > 5 cm. Unrestricted rising was related to the presence of lunge areas and brisket boards. There were fewer hock and knee lesions in straw yards than in free stalls and rising was unrestricted on farms where stalls were provided with lunge areas and brisket boards. Risk factors for increased use of orthopaedic blocks by trimmers were: an increased number of foot baths per week, more frequent trimmings per year, decreased number of extra free stalls, narrower passageways, longer distances between barns and paddocks, lower placement of neck rails, increased percentage of cows perching and heifers with dirty hindlimbs, no access to paddocks, presence of free stalls, lack of lunge areas, poor quality surfaces in front of water troughs, non-grooved feed yards, stones on tracks, increased percentage of obviously ill cows, scraping passageways using tractors and the presence of grooved alleys in milking parlours. The results provide a framework for hypotheses for future investigations of risk factors for impaired locomotion.